PENGUASAAN TANAH BEKAS HAK EIGENDOM VERPONDING SETELAH BERLAKUNYA UNDANG – UNDANG POKOK AGRARIA (STUDI KASUS PUTUSAN MAKAMAH AGUNG NOMOR: 1401 K/Pdt/2018) - Geraldus Sulianto; Hanafi Tanawijaya (Jurnal Hukum Adigama, 2020)
The ownership of the land of the former eigendom Verponding  depending on rights by the residents is physical which after the enactment of the Basic Agrarian Law becomes state land which is then issued a certificate of building rights by PT.  Asuransi Jiwasraya (Persero).  How is the legal protection for residents who control the land which ex-eigendom depends rights physically after the enactment of the Basic Agrarian Law and which has been issued in the name of PT.  Asuransi Jiwasraya (Persero)?  Researchers examined these problems using normative legal research methods.  In essence, research is carried out by examining library materials or secondary data consisting of primary legal materials, secondary legal materials, and non-legal materials.  The research data shows that there are weaknesses and legal errors from the application of these cases.  This resulted in the land that had been controlled by residents for decades to change ownership to land owned by PT.  Asuransi Jiwasraya (Persero), which residents should have priority rights to the land